Enduring silence: racialized news values, white supremacy and a national apology for child sexual abuse - Tanja Dreher; Lisa Waller (2022)
This article examines news coverage of Australia's 2018 National Apology to Victims of Institutional Child Sexual Abuse to reveal how conventional news values and practices produce racialised hierarchies of media attention that routinely position whiteness at the pinnacle. Via content analysis of media coverage, informed by critical discourse analysis, we focus on whether news reporting of the Apology reflected the Royal Commission's stated commitment, care and attention to ensuring First Nations people, who were over-represented among victims and survivors of institutional child sexual abuse, were afforded voice and agency in media. The coverage was remarkable for its failure to connect the 2018 Apology to the 2008 Apology to the Stolen Generations, or to ongoing concerns regarding high rates of Indigenous child removal and over-incarceration. Overall, we argue that news values and routines work to structure media representation through logics of white supremacy and relegating colonial violence to the past.